Studies on the Distribution Pattern of Medicinal Plants of Chhattisgarh Forest Division - Tiwari, R.K.S.; Shambharkar, Vishal B.; Singh, Vinay; Ojha, B.M. (Indian Journal of Agroforestry, 2020)
Forests of Chhattisgarh are rich in tree, shrub, herb and climber species of medicinal importance. Three forest divisions i.e. Bilaspur, Jashpur and Bastar of Chhattisgarh were surveyed to study the distribution pattern of medicinal plants and their potential sites. 137 species from fifteen study sites are discussed here in respect to their density, abundance and diversity index. Sites, namely Kurandi and Majhkot mixed forest area (Jagdalpur, Bastar) were rich in medicinal plant (91 species), while Chhaparva and Lamni (Bilaspur) these have only 10 species. Important species like Athyrium falcatum Curcuma aromatica, Curcuma angustifolia, Flemengia nana, Elephantoplus scaber, Embelia tsjeriam, Lees aspera, Lantana camera and Vitis tomentosa were recorded in high density (scale-3) with high frequency (above 0.80), high relative abundance (above 1.12) and high occurrence (above 190 plants). Where as Abrusprecatorius, Alangium atrifolium, Argyreria speciosa, Aristolochia indica, Curcume caesia, Gymneme sylvestre, Hedychium coronarium, Milingtonia hortensis, Plumbago zeylanica and Rauwolfia serpentina have been found in low density (scale 1), low frequency (0.07) and low relative abundance (below 0.4). Withania somnifera (Ashwagandha) was not recorded in survey sites. The potential sites need to be given more attentions in respect of protection and conservation.